OP0287 Gene enhancers associated with an increased risk of developing jia fail to down regulate runx1 after cell stimulation. (12th June 2018) - Yarwood, A.; Taylor, C.; Hinks, A.; Smith, S.; Duffus, K.; McGovern, A.; Thomson, W.; Eyre, S.
Abstract : Background: In recent years there have been tremendous strides in determining the genetic component of complex diseases, not least in Juvenile Idiopathic Arthritis (JIA). We now have 17 genetic loci robustly associated with an increased risk for developing JIA. 1 In JIA, like all complex diseases, the regions of the genome harbouring genetic changes are found outside protein coding DNA, in regions of the genome shown to control gene expression, often sited some distance from the closest gene. One of these JIA associated regions, on chromosome 21q22, is labelled with the RUNX1 gene, although the associated variants are situated over 450 kb from the gene. We have previously demonstrated, through Capture HiC analysis, that the genomic region containing the JIA associated variants makes a physical contact with the RUNX1 promoter. The next challenge in this region, therefore, is to determine how a risk genetic background effects the expression of the gene, contributing to the susceptibility to JIA. Objectives: Determine the function and mechanism of how the gene enhancer region, situated over 450 kb upstream of the RUNX1 gene, works to increase the risk of developing JIA. Methods: B-lymphocyte cell lines, containing either a risk or protective JIA genetic background at the 'RUNX1' loci were interrogated for potential causative functional mechanism. Allele specific interactions were investigated using chromosome conformation capture (3C), enhancer activity (H3K4me1) with chromatin immunoprecipitation (ChIP), and the resultant expression of the RUNX1 gene analysed by qPCR in both stimulated (IL4/anti CD40) and unstimulated cell lines. Results: The enhancer region associated with JIA interacts with the RUNX1 promoter in B-cell lines. A stimulation specific effect is observed in B-cell lines harbouring the protective alleles. In this protective context, prior to stimulation RUNX1 expression is higher than in the risk genotype with enhancer enrichment detected near the proximal promoter. After stimulation the interaction between the enhancer and RUNX1 promoter is much stronger, and whilst no enhancer enrichment was detected, this increased interaction frequency after stimulation corresponds to a sharp downregulation of RUNX1 expression. In contrast, the risk genotype showed no stimulation dependant change, maintaining both interaction and expression levels. Conclusions: 3C and ChIP experiments were performed to investigate genotype and stimulation specific DNA-DNA and DNA-protein interactions and identify correlation with gene expression.These results suggest that the ability for B-cells to switch from relatively high expression of the RUNX1 transcript to low expression upon stimulation is crucial to an appropriate immune response. Reference: [1] Hinks A, et al. Dense genotyping of immune-related disease regions identifies 14 new susceptibility loci for juvenile idiopathic arthritis. Nat Genet2013Jun;45(6):664–9. Disclosure of Interest: None declared